1998
DOI: 10.1039/a702743e
|View full text |Cite
|
Sign up to set email alerts
|

Partial Synthesis of (−)-11,12-Dinordriman-8-one and the (−)-Enantiomer of Polywood†

Abstract: Partial Synthesis of ()-11,12-Dinordriman-8-one and the ()-Enantiomer of Polywood †

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
(20 reference statements)
1
7
0
Order By: Relevance
“…Enone 3 had previously been prepared by a direct oxidation of 1 with PCC. 12 Enone 3 showed an optical rotation of C2.47 (c D 20.21, CHCl 3 ), in agreement with the value previously reported by Hlubucek et al 4 Polygonone (6) was obtained by a similar sequence as that described above for 3, starting from diol 12, 16 which was submitted to a selective protection of the allylic OH at C-12 with tertbutyldiphenylsilyl chloride (TBDPS-Cl) (97% yield) to give crude 994 Spectral Assignments and Reference Data Tables 1 and 2 show the complete, unambiguous assignments of the 1 H and 13 C spectra, respectively, for compounds 3, 6, 13 and 17.…”
Section: Resultssupporting
confidence: 68%
“…Enone 3 had previously been prepared by a direct oxidation of 1 with PCC. 12 Enone 3 showed an optical rotation of C2.47 (c D 20.21, CHCl 3 ), in agreement with the value previously reported by Hlubucek et al 4 Polygonone (6) was obtained by a similar sequence as that described above for 3, starting from diol 12, 16 which was submitted to a selective protection of the allylic OH at C-12 with tertbutyldiphenylsilyl chloride (TBDPS-Cl) (97% yield) to give crude 994 Spectral Assignments and Reference Data Tables 1 and 2 show the complete, unambiguous assignments of the 1 H and 13 C spectra, respectively, for compounds 3, 6, 13 and 17.…”
Section: Resultssupporting
confidence: 68%
“…It is known that 9-epi-polygodial is formed from polygodial by base-treatment (Cortés et al, 1998;Kubo and Ganjian, 1981), and there are other reports of this compound being an artifact of the GC-MS analysis (Asakawa et al, 2001). We confirmed that upon injection of a 1 H NMR verified reference standard of pure polygodial, also 9-epi-polygodial is observed, and that the ratio of the peaks versus 9-epi-polygodial varied from 1.6 to 0.8:1 depending on the injection temperature (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The compounds 15–18 were synthesized via the common starting material polygodial (2) as detailed below ( Scheme 2 ). Their structures were established by comparison with the previously reported spectral data for the same compounds [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%